Retinal organoids from human-induced pluripotent stem cells: From studying retinal dystrophies to early diagnosis of Alzheimer's and Parkinson's disease. (30th July 2023) - Móvio, Marília Inês; de Lima-Vasconcellos, Théo Henrique; dos Santos, Gabrieli Bovi; Echeverry, Marcela Bermudez; Colombo, Elisabetta; Mattos, Leonardo S.; Resende, Rodrigo Ribeiro; Kihara, Alexandre Hiroaki
Abstract: Human-induced pluripotent stem cells (hiPSCs) have provided new methods to study neurodegenerative diseases. In addition to their wide application in neuronal disorders, hiPSCs technology can also encompass specific conditions, such as inherited retinal dystrophies. The possibility of evaluating alterations related to retinal disorders in 3D organoids increases the truthfulness of in vitro models. Moreover, both Alzheimer's (AD) and Parkinson's disease (PD) have been described as causing early retinal alterations, generating beta-amyloid protein accumulation, or affecting dopaminergic amacrine cells. This review addresses recent advances and future perspectives obtained from in vitro modeling of retinal diseases, focusing on retinitis pigmentosa (RP). Additionally, we depicted the possibility of evaluating changes related to AD and PD in retinal organoids obtained from potential patients long before the onset of the disease, constituting a valuable tool in early diagnosis. With this, we pointed out prospects in the study of retinal dystrophies and early diagnosis of AD and PD.